State dependence in labor market fluctuations - Carlo Pizzinelli; Konstantinos Theodoridis; Francesco Zanetti (Cardiff University, Cardiff Business School, 2020)
This paper documents state dependence in labor market fluctuations. Using aThreshold Vector Autoregression model (TVAR), we establish that the unemployment rate, the job separation rate, and the job finding rate exhibit a larger response to productivity shocks during periods with low aggregate productivity. A Diamond-Mortensen-Pissarides model with endogenous job separation and on-the-job search replicates these empirical regularities well.We calibrate the model to match the standard deviation of the job-transition rates explained by productivity shocks in the TVAR,and show that the model explains 88 percent of the state dependence in the unemployment rate, 76 percent for the separation rate and 36 percent for the job finding rate.The key channel underpinning state dependence in both job separation and job finding rates is the interaction of the firm's reservation productivity level and the distribution of match-specific idiosyncratic productivity. Results are robust across several variations to the baseline model.
Keywords: E24; E32; J64; C11; 330; Search and Matching Models; State Dependence in Business Cycles; Threshold Vector Autoregression